SO SÁNH SỰ XUẤT HIỆN CỦA SPREAD F XÍCH ĐẠO TỪ TRONG NĂM MẶT TRỜI HOẠT ĐỘNG TRUNG BÌNH (2003) VÀ HOẠT ĐỘNG YẾU (2005) - Lan, Hoàng Thái; Trang, Nguyễn Thu; MACDOUGALL, JOHN (Vietnam Journal of Earth Sciences, 2011)
The occurrence of equatorial spread F over Ho Chi Minh City in years 2003 and 2005This paper presents results of the study of spread F based on the ionograms obtained at Ho Chi Minh City (Vietnam)for year 2003 (medium solar activity) and year 2005 (weak solar activity) under quiet geomagnetic conditions.The characteristics of Spread F over Vietnam showed a tendency with a decrease and later occurrence in the year of weaker solar activity. The seasonal variations showed maximum in March - April and minimum in December.The Range Spread F (Fs_Q) that related to scintillations of radio signals between satellites and ground stations occurred pre-midnight and appeared more in February, March and April. The time of appearance of the Fs_Q in the year 2005 occurred later than in the year 2003.The Frequency Spread F (Fs_F) occurred post-midnight and showed maximum of occurrence during equinoxial months.These results were also compared with results of other equatorial stations.